Benzocyclobutene‐containing Carbosilane Monomers as a Route to Low‐κ Dielectric and Low Dielectric Loss Materials. Issue 15 (20th April 2022) - Shi, Qingyu; Peng, Qiuxia; Wu, Song; Long, Quan; Deng, Yueting; Huang, Yawen; Ma, Jiajun; Yang, Junxiao
Abstract: A benzocyclobutene (BCB) monomer containing carbosilane (CS‐BCB) was successfully synthesized from 4‐vinyl benzocyclobutene (4‐VBCB) and 3, 6‐bis(dimethylsilyl)benzocyclobutene (3, 6‐D(DMHS)BCB) by hydrosilylation in the presence of Karstedt's catalyst. As an improvement to the conventional synthesis method, the carbosilane is obtained in only two steps. In addition, this method avoids the use of halogens and Grignard reagents, which are expensive and environmentally damaging. After ring‐opening polymerization, the resultant cured CS‐BCB resin shows excellent thermal and dielectric properties; specifically, the 5 % weight loss temperature (T5% ) is 435 °C, the dielectric constant (D k ) is 2.36, and the dielectric loss (D f ) is less than 10 −3 at 10 MHz. Thus, this polymer has enormous potential as a high‐performance electronic interlayer material. Abstract : In this study, a two‐step method that avoids the need for bromination and Grignard reaction and is thus more economical and environmentally benign, was adopted to obtain the target product. The CS‐BCB monomer was obtained from 3, 6‐D(DMHS)BCB and 4‐VBCB by hydrosilylation. The resultant cured resin exhibits good dielectric, mechanical, and thermal properties.